Japanese Amusement Arcades in the Retro Video Game Segment: A Case of Survival Strategy - Takei, Hideki (Business Management and Strategy, 2021)
Amusement arcades called Game-centers have tried to find ways of surviving in Japan. Independent game-centers with limited financial capacities have mostly struggled to find the best possible way to survive (Livedoor, 2015; Thutmosev, 2015; Nomu, 2016; SPEEDA, 2017; Chiba, 2018; Kamohara, 2019). For them, a niche strategy may be the best possible strategic direction to survive (Thutmosev, 2015; Sankei, 2016; Hirakawa, 2019; Kamohara2, 2019). This paper will focus on game-centers’ strategies in the retro video game niche to develop a general model of game-centers’ survival strategies. We will then refine the model through interviews with senior-level employees of Japan’s most successful retro game-center.